MENINGKATKAN KEBERLANJUTAN PERTANIAN ORGANIK MELALUI PELATIHAN SEKOLAH LAPANG TANI DI KABUPATEN KARANGANYAR, INDONESIA - Agung Prasetyo; Suswadi; Moh. Erkamim; Alina Dian Aryani; Muhamad Nur Fadhilah (Jurnal Abdi Insani, 2025)
The use of chemical inputs in agriculture has generated negative impacts on the environment, human health, and the sustainability of food systems, thereby encouraging the development of environmentally friendly and organic farming. Karanganyar Regency, through regulations and the establishment of the Karanganyar Organic Farmers Association (APOKAT), has demonstrated strong commitment to organic farming development. However, practices in the field still face challenges, particularly in production aspects, where some farmers have not consistently implemented Standard Operating Procedures (GAP-GHP). This condition poses risks of declining productivity and the sustainability of organic farming areas. To address these issues, a community service program was carried out from August to October 2024 in Mojogedang District, Karanganyar. The methods included GAP and GHP socialization, farmer field schools, demonstration plot management, training on organic input production, and focus group discussions (FGD). The participants consisted of 25 pioneer farmers representing groups under APOKAT. Farmers’ knowledge was evaluated through pre-tests and post-tests using a Likert scale. The results showed a significant improvement in farmers’ knowledge, with the average score increasing from 3.13 to 4.57. The improvement covered all indicators, particularly land preparation and crop maintenance. Furthermore, correlation analysis indicated a significant positive relationship between increased farmers’ knowledge and the sustainability of organic farming, with the environmental dimension being the highest. In conclusion, this program not only enhanced farmers’ capacity in implementing GAP and GHP for organic rice farming but also strengthened the sustainability of organic agriculture in Karanganyar. These results may serve as a best practice model for other regions in developing sustainable organic farming.